2017
DOI: 10.47102/annals-acadmedsg.v46n5p185
|View full text |Cite
|
Sign up to set email alerts
|

Road Crashes in Older Persons and the Use of Comorbidity Polypharmacy Score in an Asian Population

Abstract: Introduction: Age-related physiological changes predispose older road users to higher mortality from traffic crashes. We aimed to describe the injury epidemiology of these patients, and explore the association between the comorbidity polypharmacy score (CPS) and outcomes. Materials and Methods: This retrospective study utilised data from the Trauma Registry in the National University Hospital, Singapore, between January 2011 and December 2014. Patients involved in traffic crashes aged 45 years and above with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Some studies have suggested age as an independent factor that can be used to predict outcomes. [19][20][21] Similar to findings in other studies, elderly patients in our study had more comorbidities than young patients. 22,23 The increase in comorbidities in young and elderly patients between 2004 and 2015 might be attributed to the promotion of health screening by the authorities and cheaper screening tests that were made widely available to residents in Singapore.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies have suggested age as an independent factor that can be used to predict outcomes. [19][20][21] Similar to findings in other studies, elderly patients in our study had more comorbidities than young patients. 22,23 The increase in comorbidities in young and elderly patients between 2004 and 2015 might be attributed to the promotion of health screening by the authorities and cheaper screening tests that were made widely available to residents in Singapore.…”
Section: Discussionsupporting
confidence: 88%
“…The CPS was first reported in 2011 [1]. It assigns one point for each disease process or comorbidity and one point for each drug the patient is taking before admission; there is no maximum score [9][10][11]. The primary characteristic of CPS is that it encompasses all disease processes and evaluates their severity based on the number of medications.…”
Section: Introductionmentioning
confidence: 99%